THE NEED FOR PLANNING MULTI-STOREY PARKING PLACES IN LARGE CITIES OF OUR REPUBLIC - Rakhmatova , Gulhayo (Techscience uz - Topical Issues of Technical Sciences, 2025)
This article highlights the necessity of planning multi-level parking facilities in the context of major cities in Uzbekistan. Key factors include the growing number of vehicles, limited land availability, and environmental concerns. The article offers recommendations adapted to local infrastructure, based on international practices.